The Role of Academics as Agents of Change in Accelerating Rural Community Development - Isra Misra; Ali Sadikin; Muhammad Yusuf; Isnawati Isnawati; Wahyu Andika; Noviana Noviana (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to increase community participation in village development in Tabiku Village, Seruyan Raya District, Seruyan Regency, through program-based approaches such as community skills training in the agricultural sector, tourism potential development, and increasing health awareness. The implementation method applied in this service activity was Participatory Action Research (PAR), beginning with preparation, observation, training, and mentoring. Data were collected through observation, interviews, and documentation methods. The results of the activity indicate a positive response and high active participation from the community in implementing the jointly designed programs. Although some activities were not carried out exactly as planned due to adjustments to village conditions, the programs were implemented smoothly and effectively. The conclusion of this community service activity is that collaboration with the village government has been quite effective in enhancing village development. The recommendation from this activity is the need for synergy among the village government, the private sector, and the local community to increase awareness and concern for sustainable village development.